RELIGIOUS AND CULTURAL DEMARCATION: THE MYSTICISM DIMENSION IN THE PAJONJONG BAGAS TRADITION BY THE BATAK ANGKOLA MUSLIM COMMUNITY - Hasibuan, Armyn; Miswari, Miswari; Nasution, Ismail Fahmi Arrauf (Universitas Islam Negeri Ar-Raniry, 2024)
Abstract This study aims to determine the mystical dimensions of the pajonjong bagas ceremony, a series of rituals in building a new house, as part of the culture of the Batak Angkola community. In this traditional ceremony, several rituals contain mystical elements, to influence the beliefs of Ahlu Sunnah wal Jama'ah. Based on the qualitative study, an ethnographic approach was employed, with data obtained through observation, interviews, and documentation of the entire pajonjong bagas ceremonial processes in the Batang Angkola sub-district, South Tapanuli. The results showed that the pajonjong bagas encompassed a high philosophical value and were highly beneficial for the community, specifically for those establishing new houses and still deeply rooted in local traditions or wisdom. However, several elements of the rituals were not explicitly studied or significant in the teachings of Islam. Various symbols were also used in the ceremony, such as coconut, sugarcane and palm sugar, chayote, and banana symbolizing usefulness, sweet speech actualization, continuity, and coolness. All these symbols were assembled and hung on the rabung bukkulan, a wooden structure used as a framework. This cultural accommodation was subsequently associated with local and Sufi mysticism.